(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A number of studies investigating the psychological concomitants to meditation have been conducted with some consistency of results obtained. An important caveat when using subjective reporting of psychological functioning is that impact of expectancy and performance motivation within meditator participants is difficult to control (West, 1987 Shapiro Walsh, 1984). Nevertheless, a number of the clinical reports—both psychological and medical—are suggestive of significant effects and together with the other psychological studies provide intriguing correlates of the meditation and brain activity findings summarized above.